Constructing Education: 1961-69 - Linzey, Kate (Architectural History Aotearoa, 2005)
The 1960s were a time of great change and growth in New Zealand's tertiary eduction sector, and the university-based discipline of architecture was in no way exempt from this progress. In response to the Parry Report of 1959-1960, the New Zealand government passed the 1961 Universities Act, which dissolved the federated University of New Zealand. This Act opened the way for the independence of the four universities of Auckland, Victoria, Canterbury and Otago, and the two allied agricultural colleges of Massey and Lincoln. Under the federated university system, Auckland University College had been the centre of architectural training, and had delivered extramural course through colleges in the other centres. As the "disproportionate number" of extramural and part-time study had been criticisms levelled by the Parry Report, it was obvious that another School of Architecture would now be required, but where? Ever an argumentative association, members of the New Zealand Institute of Architects engaged in a lively debate on the choice, positing Victoria University in Wellington, and Canterbury University in Christchurch, as the major contenders. By the end of the decade university-based architectural training would expand at both Auckland and (the new) Wellington Schools, New Zealand's first PhD in Architecture would be conferred on Dr John Dickson, and many of the careers of architects and architectural academics who went on to construct the discipline as it is today, had begun.